Measuring self-rated health status among resettled adult refugee populations to inform practice and policy - a scoping review - Alison Dowling; Joanne Enticott; Grant Russell (BMC, 2017)
Abstract Background The health status of refugees is a significant factor in determining their success in resettlement and relies heavily on self-rated measures of refugee health. The selection of robust and appropriate self-rated health measurement tools is challenging due to the number and methodological variation in the use of assessment tools across refugee health studies. This study describes the existing self-report health measures which have been used in studies of adult refugees living in the community to allow us to address the challenges of selecting appropriate assessments to measure health within refugee groups. Methods Electronic databases of Ovid Medline, CINAHL, SCOPUS, Embase and Scopus. Results This review identified 45 different self-rated health measurements in 183 studies. Most of the studies were cross sectional explorations of the mental health status of refugees living in community settings within Western nations. A third of the tools were designed specifically for use within refugee populations. More than half of the identified measurement tools have been evaluated for reliability and/or validity within refugee populations. Much variation was found in the selection, development and testing of measurement tools across the reviewed studies. Conclusion This review shows that there are currently a number of reliable and valid tools available for use in refugee health research; however, further work is required to achieve consistency in the quality and in the use of these tools. Methodological guidelines are required to assist researchers and clinicians in the development and testing of self-rated health measurement tools for use in refugee research.